2007
DOI: 10.1111/j.1742-1241.2006.01242.x
|View full text |Cite
|
Sign up to set email alerts
|

Response to pioglitazone treatment is associated with the lipoprotein lipase S447X variant in subjects with type 2 diabetes mellitus

Abstract: To investigate the influence of the S447X variant in lipoprotein lipase (LPL) gene on the response rate to therapy with the thiazolidinedione pioglitazone. A total of 113 diabetic patients were treated with pioglitazone 30 mg for 10 weeks. Response to the pioglitazone treatment was defined by either a >10% relative reduction in fasting blood glucose (FBG) or a more than 1% decrease in glycosylated haemoglobin (HbA1c) values after 10 weeks of pioglitazone treatment. The genotypes were determined by polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 23 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…These results are in agreement with those of Abd El-Haleim et al (36) and also indicate that treatment with TZD has a significant role on the serum lipid profile, as suggested by Wang et al (37). However, it has been previously reported that TZD administration may lead to deteriorating microvesicular steatosis and raised hepatic TG levels, through decreasing blood TG and free fatty acid (23).…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with those of Abd El-Haleim et al (36) and also indicate that treatment with TZD has a significant role on the serum lipid profile, as suggested by Wang et al (37). However, it has been previously reported that TZD administration may lead to deteriorating microvesicular steatosis and raised hepatic TG levels, through decreasing blood TG and free fatty acid (23).…”
Section: Discussionsupporting
confidence: 93%
“…Lipoprotein lipase is the rate-limiting enzyme for the breakdown of lipoproteins rich in triglycerides (Groenemeijer et al, 1997). Lipoprotein lipase is synthesized by and secreted from various parenchyma cells including adipocytes, muscle cells, and macrophages and expression was increased by PIO in a previous in vivo study (Bogacka et al, 2004; Wang et al, 2007). Among more than 40 polymorphisms in LPL gene, S447X is the most extensively studied polymorphism; it causes a premature stop codon and the elimination of serine and glycine at the C-terminal (Wang et al, 2007).…”
Section: Resultsmentioning
confidence: 83%
“…Lipoprotein lipase is synthesized by and secreted from various parenchyma cells including adipocytes, muscle cells, and macrophages and expression was increased by PIO in a previous in vivo study (Bogacka et al, 2004; Wang et al, 2007). Among more than 40 polymorphisms in LPL gene, S447X is the most extensively studied polymorphism; it causes a premature stop codon and the elimination of serine and glycine at the C-terminal (Wang et al, 2007). Previous independent studies reported an association of the S447X variant with dyslipoproteinemia and coronary artery disease (Kuivenhoven et al, 1997; Wang et al, 2007).…”
Section: Resultsmentioning
confidence: 83%
“…Polymorphism (S447X) in the LPL gene influences the beneficial effects of pioglitazone on cardiovascular complications of diabetes mellitus [80]. Such SNP mediates pioglitazone-linked increase in the synthesis and secretion of LPL in multiple types of parenchymal cells [81,82]. Studies have further shown that the S447X variant is intrinsically associated with the pathogenesis of dyslipoproteinemia and coronary artery disease and thus markedly reduces the efficacy of pioglitazone in the LPL S447X genotype when compared with subjects with the S447S genotype [82].…”
Section: Pharmacogenomics and Pharmacogenetics Of Pioglitazone In Diabetesmentioning
confidence: 99%